Circular economy (CE) implementation framework development and application to reverse osmosis (RO) membrane desalination systems - Anim-Mensah, Alexander R. (Frontiers in Membrane Science and Technology, 2025)
The circular economy (CE) is gaining attention globally, given its potential to contribute significantly toward sustainable development. The demands for cleaner and safer water amid rising waterborne diseases and stringent environmental regulations are driving the need for reverse osmosis (RO) membrane desalination processes. RO membrane desalination processes are associated with extensive material and energy use, with resulting waste generation, and have ever-growing ecological footprints. Extensive theoretical knowledge on CE and sustainability exists, although it lacks the practical bridge to implementation. In this article, a structured and practical framework is developed and applied to an RO membrane desalination system. Features of this framework allowed breaking the RO membrane desalination system into phases of design (DP), manufacturing (MP), use (UP), and end-of-life (EoLP) and assessing it against both the 3R and 9R ladder strategic frameworks. The resulting CE and sustainability importance trend in the order of DP > MP > UP > EoLP allows for setting the initial implementation starting point, phase(s), or stage(s) for prioritization and maximization to overcome some of the initial implementation challenges. This opens the door for continuous improvements and incremental progress to take on an entire circular or sustainability project in the long term. CE broken into implementation clusters of circular business models (CBM), resource efficiency strategies (RES), and regenerative sustainability practices (RSP), assessed against each of DP, MP, UP, and EoLP phases, offered valuable insights into myriads of opportunities associated with RO membrane desalination system CE implementation. The framework provides step-by-step guidance to bridge the gap between CE and sustainability theoretical knowledge and practical implementations for industrial adoption to reap the countless opportunities.